The international status of education about the Holocaust : a global mapping of textbooks and curricula - Carrier, Peter (Unesco, 2015)
This publication documents the ways in which the Holocaust is presented in secondary school level history and social studies curricula worldwide, and conceptualized and narrated in textbooks from twenty-six countries, with all continents represented. Historical understandings of the Holocaust are defined in terms of the spatial and temporal scales with which the event is portrayed, the protagonists involved, interpretative patterns (according to definitions, comprehensiveness, causes, relativization or banalization), narrative techniques and viewpoints, didactic methods, and national idiosyncrasies. The study is based on 272 currently valid curricula from 135 countries, and on 89 textbooks published in 26 countries since 2000. The aim of the study is primarily to document information in such a way that it reflects local understandings of the Holocaust, principally by recording concepts and narratives of the Holocaust found in educational media currently in use in schools. The findings show both convergence and divergence in the representations analysed. The Holocaust is subject to shared patterns of representation, which include selectivity, personalization, appropriation, screening and omission. It is also subject to narrative idiosyncrasies. One of the main trends worldwide is domestication, a process whereby countries place emphasis on the local significance of the event or appropriate them in the interests of local populations. Drawing on such national and international patterns of representation, the publication concludes by formulating recommendations for future curricula and textbook narratives about the Holocaust. These recommendations relate to such issues as the use of terms, the comprehensiveness of historical facts, the definition of causes, the combination of universal and local approaches, and the development of historical literacy.